Setting conservation priorities when what you see is not what you get. (21st January 2013) - Vellend, Mark; Kharouba, Heather M.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Mapping the potential extinction debt of butterflies in a modern city: implications for conservation priorities in urban landscapes Other Commentaries on this paper: Extinction debt at different spatial scales Response from the authors: From ecological pessimism to conservation chance: reviving living dead in changing landscapes